The realization of security policy in the system of executive power of the Russian Federation - Dmitry Sokolov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2016)
This article is devoted to topical issues of implementation of the state policy in the field of information security activities of the Government. The author believes that the development of an information society presupposes the solution of priority tasks of free search, receipt, production and dissemination of information for every member of society, media development, the formation of public information resources to provide accessible information services, provision of conditions for the establishment, development and operation of information systems, formation of a single information space of the country and its integration into the global information space. The author also notes the need to build in a system of government objectives and strategies for implementing the idea of "electronic government".